A formal model for the functional test of software to achieve maturity integrated level 2 - Escobar-Sánchez, Milton Eduardo; Fuertes-Díaz, Walter Marcelo (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Software applications are becoming increasingly important for organizations because they allow to accomplish its core tasks efficiently. Therefore, it is compulsory to test the software quality. This research focuses on designing a formal model for the development of a functional software testing, that would achieve level 2 of Test Maturity Model Integrated (TMMI). To carry out this work, we started with a situational analysis using ISO-9001-2000. Then, several software quality models as ISO/IEC 9126, were reviewed. Also the main quality standards for software testing as TMM, TMMI, Test Process Improvement (TPI), and Test Management Approach (TMAP) were compared, based on some criteria such as the year of publication, licensing, defined levels, factories and risks. With this information a proposed model which is independent of the software development process was designed. It is based on the test cycle and it has been divided of four parts: Specification, Planning, Execution, and Evaluation. To validate this model, it was applied to a SMEs as a case of study. The results show the model efficiency. Also reveal that it is necessary to develop an organizational culture of quality within the company.